The relative proportions of water group ions in Saturn's inner magnetosphere: A preliminary study. Issue 8 (12th August 2015) - Wilson, R. J.; Bagenal, F.; Cassidy, T.; Fleshman, B. L.; Crary, F.
Abstract: We present a technique to gather ion composition information in the form of relative abundances of the water group ion species in Saturn's inner magnetosphere, utilizing the Cassini Plasma Spectrometer's Straight‐Through Time‐of‐Flight data from two orbits in 2011. We show that between 4.75 and 8 Saturn radii H2 O + ions dominate the water group species, and from 8 to 10 Saturn radii it is OH + ions that dominate. Our results show that the relative proportion of H3 O + falls fastest with increasing distance, while the proportion of H2 O + decreases slowly. However, O + and OH + increase with distance, and O + is the least dominant ion species out to eight Saturn radii outside of which it is comparable to H3 O + . The relative abundance of H2 O + found here matches theoretical work based on Herschel telescopic data very well. These results are compared with other published work, and further improvements to the technique are discussed. Key Points: A technique to estimate relative abundance of water group ion species within CAPS data is provided Does not require model line profiles for each species at each energy Computationally quick and easy to apply